Antibiotic Resistance of Salmonella spp. Isolated from Shrimp Farming Freshwater Environment in Northeast Region of Brazil. (22nd December 2013) - Carvalho, Fátima C. T.; Sousa, Oscarina V.; Carvalho, Edirsana M. R.; Hofer, Ernesto; Vieira, Regine H. S. F.
Abstract : This study investigated the presence and antibiotic resistance of Salmonella spp. in a shrimp farming environment in Northeast Region of Brazil. Samples of water and sediments from two farms rearing freshwater-acclimated Litopenaeus vannamei were examined for the presence of Salmonella . Afterwards, Salmonella isolates were serotyped, the antimicrobial resistance was determined by a disk diffusion method, and the plasmid curing was performed for resistant isolates. A total of 30 (16.12%) of the 186 isolates were confirmed to be Salmonella spp., belonging to five serovars: S . serovar Saintpaul, S . serovar Infantis, S . serovar Panama, S . serovar Madelia, and S . serovar Braenderup, along with 2 subspecies: S. enterica serovar houtenae and S. enterica serovar enterica. About twenty-three percent of the isolates were resistant to at least one antibiotic, and twenty percent were resistant to at least two antibiotics. Three strains isolated from water samples (pond and inlet canal) exhibited multiresistance to ampicillin, tetracycline, oxytetracycline, and nitrofurantoin. One of them had a plasmid with genes conferring resistance to nitrofurantoin and ampicillin. The incidence of bacteria pathogenic to humans in a shrimp farming environment, as well as their drug-resistance pattern revealed in this study, emphasizes the need for a more rigorous attention to this area.